An autonomous decentralized voltage control scheme in PEV charging devices on the distribution network– reactive power compensation for voltage decreases caused by household loads and charging devices. (28th December 2012) - Su, Su; Jiang, JiuChun; Wang, Wei
SUMMARY Plug‐in electric vehicles (PEVs) will spread as environmental awareness continues to grow. As a result, many PEV batteries are likely to be charged in residential areas overnight, but this will cause a significant voltage decrease in the distribution network. As a countermeasure that does not require capital investment to strengthen the network, this paper proposes an autonomous decentralized voltage control scheme using a PEV battery charger. The scheme can continuously estimate household loads consumption and calculate the reactive power required for compensating the voltage decreases caused by household load consumption and PEV charging. Because only the measured voltage and current at the connecting point of the PEV battery and the impedance between this point and the nearest distributing substation are required to calculate the necessary amount of reactive power compensation, the control scheme can be implemented merely by modifying the control logic circuit built into the PEV battery charger at almost no extra cost. A realistic model of the distribution network and the standard daily demand curve in residential areas in Japan are used to validate the performance of the new scheme. Copyright © 2012 John Wiley & Sons, Ltd.